1954
DOI: 10.1002/cber.19540870417
|View full text |Cite
|
Sign up to set email alerts
|

Umsetzungen von Halogenverbindungen mit Formamid (Formamid‐Reaktionen, III. Mitteil.)

Abstract: Die Umsetzung von Halogenverbindungen mit Formamid bei 150° liefert entweder Formiate oder Formylamine. Priiparative Hedeutung hat die Damtellung von a-Oxy-und a-Formoxy-carbonsiiureestern. Zur Erkliirung der zwei verschiedenen Reaktionsmoglichkeiten des Formamids werden Mechanismen aufgeskllt, welche die Versuchsergebnisse hefriedigend wiedergeben. Den Ausgangspunkt dieser Arbeit bildeten sich widersprechende Angaben von J. L. E. Erickson') und R. M. J o y c e 2 ) . Erickson setzte Halogenverbindungen, z.B. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1970
1970
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…[99] As shown in Table 6, the alkylation of formamide with noctyl bromide, a classical S N 2 substrate, yields the O-alkylated formamide selectively, whereas the tritylium cation leads to selective N-alkylation. [100] Gompper and Christmann concluded that S N 2 reactions as well as S N 1 reactions with "instable carbenium ions" occur preferentially at the oxygen atom, while S N 1 reactions with "stable carbenium ions" take place at the nitrogen terminus. [101] In the reactions with stable carbenium ions, the initial O attack at the neutral amide is reversible and subsequent rearrangement to the thermodynamically more stable amides takes place.…”
Section: Amides and Amide Anionsmentioning
confidence: 99%
“…[99] As shown in Table 6, the alkylation of formamide with noctyl bromide, a classical S N 2 substrate, yields the O-alkylated formamide selectively, whereas the tritylium cation leads to selective N-alkylation. [100] Gompper and Christmann concluded that S N 2 reactions as well as S N 1 reactions with "instable carbenium ions" occur preferentially at the oxygen atom, while S N 1 reactions with "stable carbenium ions" take place at the nitrogen terminus. [101] In the reactions with stable carbenium ions, the initial O attack at the neutral amide is reversible and subsequent rearrangement to the thermodynamically more stable amides takes place.…”
Section: Amides and Amide Anionsmentioning
confidence: 99%
“…The α-hydroxy ketone 25 was prepared analogously to the method described by Brousse and Lefort by oxidation of methyl cis-9,10-epoxyoctadecanoate (21) with dimethyl sulfoxide at 90Ϫ100°C in the presence of boron trifluorideϪdiethyl ether. [17] In a Bredereck reaction [18] the α-hydroxy ketone 25 was treated with formamide to afford the imidazoles 26 and the oxazoles 27 (Scheme 6).…”
Section: Resultsmentioning
confidence: 99%
“…Another observation of complexes from the reaction of DMF or N -methylformamide (NMF) with alkylating agents comes from the early work of Bredereck and co-workers . Solid addition compounds were isolated from NMF or DMF and dimethyl sulfate, analogous to that mentioned above.…”
Section: Discussionmentioning
confidence: 98%